2009
DOI: 10.1111/j.1095-8649.2009.02338.x
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variability in lunar spawning rhythms: absence of a lunar pattern in the northern mummichog Fundulus heteroclitus macrolepidotus

Abstract: In this study, the natural spawning season of the northern mummichog Fundulus heteroclitus macrolepidotus was examined from May to July in the lower St John River, New Brunswick, Canada (45 degrees N), through measurements of gonado-somatic index (I(G)), liver-somatic index (I(L)) and condition factor (K). I(G) increased during the prespawning phase (mean +/-s.e. 5.49 +/- 0.20%), peaked during the spawning phase (14.68 +/- 0.51%) and dropped during the regression phase (3.23 +/- 0.29%). A single peak of spawni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…Although GSIs declined quickly as the gametes were released with the start of the spawning period in December, some large females still with mature eggs apparently continued the spawning process into January. The absence of a relationship between female gonad size and body weight is a pattern consistent with asynchronous spawners with many spawning events during the spawning season (McMullin et al 2009;Barrett & Munkittrick 2010). Male GSI demonstrated a pattern consistent with a number of other species where gonadal recrudescence is initiated shortly after spawning, increases to a maximum size and then decreases slightly as sperm cells mature prior to spawning (Barrett & Munkittrick 2010).…”
Section: Trichomycterus Areolatussupporting
confidence: 66%
“…Although GSIs declined quickly as the gametes were released with the start of the spawning period in December, some large females still with mature eggs apparently continued the spawning process into January. The absence of a relationship between female gonad size and body weight is a pattern consistent with asynchronous spawners with many spawning events during the spawning season (McMullin et al 2009;Barrett & Munkittrick 2010). Male GSI demonstrated a pattern consistent with a number of other species where gonadal recrudescence is initiated shortly after spawning, increases to a maximum size and then decreases slightly as sperm cells mature prior to spawning (Barrett & Munkittrick 2010).…”
Section: Trichomycterus Areolatussupporting
confidence: 66%
“…Models were ranked by importance from top to bottom using D BIC, v 2 , and v 2 p value a Lipid mass and total length included as fixed effects in one model; a likelihood ratio test of two fixed effects compared to a model with lipid mass alone indicated the latter was important, confirming results of forward stepwise selection based on BIC b Calculated using truncated dataset (because data not available at all sites); In addition, daily growth rate data was not comprehensive enough to include in the restored with paired unrestricted marsh model near the intergradation zone between subspecies (Able and Felley 1986) and may exhibit semilunar spawning; however, even if this was the case, we collected fish from those sites during peak spawning period in the days leading up to full moon, a time when fish were likely to be actively spawning. Increased water temperature can trigger F. heteroclitus ovulation and spawning (McMullin et al 2009;Shimizu 2003;Wallace and Selman 1981). Therefore, warmer temperatures (as might develop behind tidal restrictions; Raposa 2002Raposa , 2008 may trigger earlier spawning relative to fish in paired unrestricted marshes, potentially resulting in the collection of more spent females in restricted marshes regardless of lunar phase.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…For populations north of New Jersey (i.e., the population examined in this study; Fundulus heteroclitus macrolepidotus, hereafter F. heteroclitus), semilunar spawning periodicity may be reduced or relaxed, during which oocytes may be continuously present in the ovary and spawning may occur daily on the highest tide from May-June (Petersen et al 2010;Taylor 1986;Selman 1980, 1981). In the absence of a lunar spawning rhythm for northern populations, water temperature is believed to be a primary factor that initiates ovulation and spawning (McMullin et al 2009;Wallace and Selman 1978, 1980, 1981.…”
Section: Introductionmentioning
confidence: 99%
“…Fundulus heteroclitus macrolepidotus were collected using standard minnow traps (Hubert 1989) (baited with commercial dried dog food) which were deployed in shallow water (<2 m) at low tide for 24 hours and retrieved the following day at low tide. Sampling in 2006 was based on the assumption that F. h. macrolepidotus followed a lunar spawning pattern (McMullin et al 2009). Samples were collected six days on either side of the full moon in June (9 th to 17 th ), July (8 th to 20 th ), and August (4 th to 14 th ) at sites R1 and E1 in 2006.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Couillard and Nellis (1999) reported similar variability in reproductive parameters observed in their study and suggested this variability may be due to reproductive timing and spawning variability. In a previous study, we examined the lunar spawning periodicity of F. h. macrolepidotus and identifi ed an absence of a lunar spawning rhythm, which may contribute to the challenge of using this subspecies as a sentinel (McMullin et al 2009).…”
Section: Introductionmentioning
confidence: 99%